1994
DOI: 10.1590/s1516-31801994000300006
|View full text |Cite
|
Sign up to set email alerts
|

Chronotopic and blood pressure response to oral glucose load in chagas' disease

Abstract: Cardiac chronotropic and pressor responses after an oral load of glucose were assessed in sixteen Chagasic subjects and 28 controls by means of blood pressure and pulse rate measurements. Cardiovascular response was correlated with serum insulin and glucose levels. The experiment identified a subgroup of Chagasic subjects (n = 8) with a hypoinsulinemic behavior presenting less chronotropic and pressor responses than controls. This may indicate a lower insulin activity and/or an early Autonomic Nervous System d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 0 publications
1
8
0
2
Order By: Relevance
“…In a previous study, Guariento et al 7 already observed the same situation in patients with the indeterminate form of Chagas' disease. Glucose metabolism, including insulin release, is related, at least partly, to autonomic nervous system integrity.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…In a previous study, Guariento et al 7 already observed the same situation in patients with the indeterminate form of Chagas' disease. Glucose metabolism, including insulin release, is related, at least partly, to autonomic nervous system integrity.…”
Section: Discussionsupporting
confidence: 63%
“…In a study involving chagasic patients, Guariento et al 7 showed an impaired BP and heart rate response to a glucose overload, a stimuli for insulin production.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, in considering potential mechanisms for reduced insulin secretion in the setting of T. cruz i infection, pancreatic nerve cells have been examined (dos Santos et al 1999a; dos Santos et al 2004; Guariento et al 1994; Guariento et al 1993; Oliveira et al 1993). In fact, it was suggested that neuritis and autonomic dysfunction were etiologic factors for pancreatic disease in this setting (dos Santos et al 2004).…”
Section: Evidence From Human Studiesmentioning
confidence: 99%
“…In a study designed to determine the effects of Chagas disease on cardiovascular responses to a glucose load, decreased insulin response in a subgroup of patients was observed (Guariento et al 1994). Patients with the indeterminate form of the disease were subjected to an OGTT and changes in heart rate, blood pressure as well as the “double cross index” (systolic blood pressure multiplied by heart rate) were measured.…”
Section: Evidence From Human Studiesmentioning
confidence: 99%
“…Moreover, considering the intricate relationship between different organ systems and processes, the proper cardiac autonomic dysfunction is expected to be correlated with metabolic, hormonal and functional renal disturbances. Indeed, cardiac autonomic dysfunction has been observed in chagasic subjects with either indeterminate or cardiac forms of the disease and in experimentally Trypanosoma cruzi-infected animals simultaneously with altered osmoregulation dependent on the antidiuretic hormone response 85 , altered hydroelectrolytic balance 86 and altered glucose tolerance 87 .…”
Section: Other Possible Effects Of Autonomic Dysfunctionmentioning
confidence: 99%